Harrison Forman Diary, Argentina, September 1954 - Forman, Harrison, 1904-1978 (1954)
In Ushuaia, Tierra del Fuego, Argentina, Harrison Forman, photographer and journalist, begins this diary describing his flight crossing over Rio Gallegos and the Strait of Magellan in Chile. In the naval port of Tierra del Fuego, he meets Lieutenant Commander Alcides Corvera who takes him on a tour of the former Ushuaia Prison. At the time of writing his diary, the prison had been closed and it was then the headquarters of the naval base. Forman tells of his trip to the base of Mount Olivia then his dinner with the Admiral of the Navy. The diaries are part of the Harrison Forman Papers 1931-1974 housed at the Special Collections & University Archives, University of Oregon Libraries. UWM Libraries received the dairies on a loan from the Special Collections & University Archives at the University of Oregon Libraries and digitized them to accompany the digital collection of Forman's photographs. The diaries were digitized to provide research materials for the Forman's negatives scanned as part of the NEH grant project "Saving and Sharing the AGS Library's Historic Nitrate Negative Images."